Pinoresinol diglucoside is screened as a putative α-glucosidase inhibiting compound in Actinidia arguta leaves - Kwon, Dodan; Kim, Gyoung Deuck; Kang, Wonseok; Park, Jeong-Eun; Kim, Song Hee; Choe, Eunok; Kim, Jung-In; Auh, Joong-Hyuck (Applied biological chemistry, 2014)
Actinidia arguta leaves are consumed as a popular food material in Korea and have been reported to exert beneficial effects on humans due to its constituent polyphenolic compounds. In this study, the α-glucosidase inhibitory compounds in A. arguta were screened and identified through α-glucosidase-guided fractionation and metabolomic analysis. The 50% ethanol extracts of A. arguta showed strong inhibitory effect (32.6%), which was comparable to acarbose as a positive control (30.0%). Through multiple steps of fractionation, pinoresinol diglucoside and fertaric acid were identified as the major potent compounds in A. arguta inhibiting α-glucosidase activity by liquid chromatography mass spectrometry analysis and metabolomic comparison. Particularly, because pinoresinol and its glycosides have been demonstrated as α-glucosidase inhibitory agents, pinoresinol diglucoside was proposed to be a putative key compound for α-glucosidase inhibition in A. arguta . This is the first study demonstrating the anti-diabetic effect of a pinoresinol-containing fraction of A. arguta and would be useful for its application as a natural α-glucosidase inhibitor.